GMP synthesis of carbon‐14 labelled substances. (23rd December 2015) - Filer, Crist N.; Maniscalco, Mario P.; Thayer, Sandra L.
Abstract : This review discusses the process of preparing and analyzing carbon‐14 labelled substances under good manufacturing practice. Abstract : This review discusses the process of preparing and analyzing carbon‐14 labelled substances under good manufacturing practice.